Bulk and surface structural changes in high nickel cathodes subjected to fast charging conditions. Issue 51 (21st May 2020) - Liu, Tianyi; Du, Zhijia; Wu, Xianyang; Rahman, Muhammad Mominur; Nordlund, Dennis; Zhao, Kejie; Schulz, Michael D.; Lin, Feng; Wood, David L.; Belharouak, Ilias
Abstract : A layered oxide cathode, LiNi0.6 Mn0.2 Co0.2 O2, undergoes sensible crystal expansion by losing significantly higher amounts of Li + at the end of fast charging cycles. Abstract : A layered oxide cathode, LiNi0.6 Mn0.2 Co0.2 O2, undergoes noticeable crystal expansion by losing significantly higher amounts of Li + at the end of fast charging cycles. However, the bulk structure of the cycled NMC622 is restored back to its pristine discharged state when intercalated with enough lithium ions during an electrochemical process.